Seleção de supervisor e diretor escolar no município de Piracicaba: racionalidades burocráticas ou tendências patrimonialistas? - Piccoli, Denise Fujihara (2008)
This dissertation searched to analyze be the selection of a school principal a supervisor that was implemented after the fundamental teaching municipalization in the 90 s. Therefore, it was taken as empiric base the developed actions in a city from São Paulo state from 1999 to 2006. To emphasize the progressive alternation in the recruitment of these public servants, there s a public contest of tests and titles made in São Paulo. The objective was to understand how the city organized to select supervisors and school pricipals, and how it was happened. Therefore, a group of people had participated somehow of these choices could supply the essential information for the study development. For uderstanding the measured of these selections it was based in impersonal, candidate s professional knowledge and the execution of the abstract norms established or reaffirmed the beginnings a political culture based in patrimonialism and in clientelism, characteristics of the brazilian state